The Impact of an Abortion Ban on Socioeconomic Outcomes of Children: Evidence from Romania - Pop‐Eleches, Cristian (Journal of Political Economy, 2006)
This study examines educational and labor outcomes of children affected by a ban on abortions. I use evidence from Romania, where in 1966 dictator Nicolae Ceauescu declared abortion and family planning illegal. Birth rates doubled in 1967 because formerly abortion had been the primary method of birth control. Children born after the abortion ban attained more years of schooling and greater labor market success. The reason is that urban, educated women were more likely to have abortions prior to the policy change, and the relative number of children born to this type of woman increased after the ban. However, when I control for composition using observable background variables, children born after the ban on abortions had worse educational and labor market achievements as adults.